Odpowiedzi

2010-02-28T20:44:06+01:00
3*(-1,5) =-4,5
6*(-1,5) =-9
(-10)*1,5=-15
0,8*(-5) =-4
(-3,92)*(-14,3)=56,056
0,392*(-14,3)=-5,6056
(-5605,6):143=-39,2
(3,92) * 1,43 =5,6056
(-0,143) * (-392) =56,056
5605,6 : (-39,2) =-143
2010-02-28T20:45:46+01:00
A) -4,5
b) -9
c) - 15
d) -4
e) 56,056
f) -5,6056
g) -39,2
h) 5,6056
i) 56, 056
j) -143
2010-02-28T20:46:13+01:00
3*(-1,5)=-4,5
6*(-1,5)=-9
(-10)*1,5=-15
0,8*(-5)=-4
(-3,92)*(-14,3)=56,056
0,392*(-14,3)=-5,6056
(-5605,6):143=-39,2
3,92*1,43=5,6056
(-0,143)*(-392)=56,056
5605,6:(-39,2)=-143